Governing digital trade – a new role for the WTO - Wallace Cheng; Clara Brandi (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Digitalisation is transforming the economy and redefining trade. Recently, members of the World Trade Organization (WTO) have started to discuss how trade policies and rules should be adapted to address this transformation. For example, in January 2019, 76 WTO members announced the launch of “negotiations on trade-related aspects of electronic commerce”. The scope of these e-commerce negotiations is yet to be defined, but to ban tariffs on electronic transmissions will certainly be on the priority list of WTO members such as the United States (US) and the European Union (EU). The idea of banning tariffs on electronic transmission originated at the WTO's Ministerial Conference (MC) in 1998, when Members declared that they would “continue their current practice of not imposing customs duties on electronic transmissions”. This temporary moratorium on e-commerce tariffs needs to be regularly extended, requiring a decision made “by consensus”. Members have repeatedly extended the moratorium on tariffs on “electronic transmissions”, most recently at the latest WTO MC in 2017. But the WTO e-commerce moratorium is increasingly disputed: First, while net exporters of digital products and services, typically industrialised countries, understand the tariff ban to apply to digital content, net importers interpret it as referring only to electronic carriers (e.g. CDs, electronic bits), which means that they regard themselves as permitted to impose customs duties on the content of online trade. Second, while net exporters like the US and the EU propose a permanent ban on e-commerce tariffs in order to provide greater certainty to consumers and business, arguing that the resulting revenue losses are small, net importers like India and South Africa underline that they suffer much greater revenue losses than industrialised countries and have to bear the brunt of the moratorium. Third, while industrialised countries argue that the ban on tariffs on electronic transmissions would reduce market distortions, developing countries are concerned that a permanent moratorium would limit their options to protect domestic products and services traded online. Fourth, the moratorium has stirred a debate about how to create a level playing field between domestic and foreign suppliers of digital products and services. We argue that WTO members should take the ongoing debate as an opportunity for the WTO to play an important role in redefining trade in a digitalised economy. To take up this challenge, we recommend the following: (a) WTO Members should seek agreement on what the e-commerce tariff moratorium covers and what it does not. (b) Concerns about who wins and who loses in the wake of the moratorium require deep-dive reflections. WTO members should thus not rush to make the moratorium permanent. They should consider extending it for (at least) another two years at MC12 and use this time to prepare a fully fledged agreement to replace the temporary decision and which could be called the Agreement on Digital Products and Other Services (ADPOS). (c) The WTO secretariat should actively engage in the ongoing broader discussions about taxation in the digitalised economy. New evolutions of international and national tax reforms and data-driven digital trade offer unprecedented opportunities for the WTO to reshape the trade agenda. But the WTO may be left behind in addressing the future of trade in a digitalised economy if it does not respond strategically.
Keywords: 330; Digitalisierung; Handel und Investitionen